Pulmonary tuberculosis in the elderly : diagnostic criteria and its epidemiology in old age homes - Morris, Charles David Wilkie (Division of Geriatric Medicine, 2017)
The majority of today's elderly people were primarily infected with Mycobacterium tuberculosis at a time when no effective chemotherapeutic treatment was available. With the progressive decline in cell mediated immunity that accompanies aging, the potential to reactivate a dormant lesion, or to be re-infected increases. The latter particularly applies in areas of high density living e.g. homes for the elderly. The incidence of pulmonary tuberculosis in whites in South Africa is very similar to that in industrialized countries (approximately 16/100 000). In a survey of old age homes in East London (South Africa) involving 809 white subjects the prevalence rate was found to be 1403/100 000; clusters were found in individual homes where up to 10% of residents had tuberculosis. The age specific incidence in the community for whites was 86/100 000, and in homes for the aged the incidence in 648 elderly subjects followed for 2 years was 1080/100 000. It is concluded that the elderly living in high density accommodation constitute a high-risk group for the development of the disease. The diagnosis of pulmonary tuberculosis in the elderly may be complicated by the high prevalence of atypical radiographic changes, difficulty in obtaining sputum, and the high false-negative rate of the tuberculin skin test. Thus, the value of haematological and biochemical abnormalities in 93 elderly tuberculotics, 113 elderly non-tuberculotics and 264 young tuberculotics were investigated. The results in the elderly tuberculotic patients were: Normochromic normocytic anaemia (70%), leucocytosis (55%), thrombocytosis (33%), rapid ESR in 90%, lymphopenia (22%) and monocytopenia (37%); hyponatraemia (60%), hypokalaemia (42%) and hypoalbuminaemia (83%), serum bilirubin (20%) and alkaline phosphatase, aspartic transaminase and lactic dehydrogenase are elevated in approximately 2/3 of patients. In comparison with the younger group (mean age 48 years) with cavitating tuberculosis, the prevalence of elderly patients (with generally mild and non-cavitating disease) with elevated bilirubin, alkaline phosphatase and liver enzymes was approximately 50% higher. When the results of liver enzyme elevations in the elderly tuberculotics were compared retrospectively with elderly patients with non-tuberculotic destructive lung disease, the former group had significantly higher values. The sensitivity (76%), specificity (48%) and positive predictive value (60%) suggest that liver enzyme abnormalities may provide useful contributory data in the non-invasive diagnosis of pulmonary tuberculosis in the elderly. The chest radiographs in 93 consecutive cases of bacteriologically proven pulmonary tuberculosis showed infrequent apical involvement (7%), with the most frequent abnormality being opacification of the middle and lower zones of the lungs; half the cases had a pleural reaction. cavitation occurs in only 1/3 of patients, and was sited equally in the apical zones and in the mid and lower zones. These findings contrast with the pattern of cavitating apico-posterior disease commonly seen in reactivated tuberculosis in younger adults. A series of 21 patients was studied to compare the yield of sputum smear examination with sputum culture for M. tuberculosis. Sputum production in non-cavitating disease was found to be infrequent and unpredictable and the number of bacilli is usually scanty. Repeated Culture of sputum for M. tuberculosis is required to improve the likelihood of obtaining a positive bacteriological diagnosis. On the basis of this study at least 4 negative sputum cultures are required to exclude the disease. In a study of 10 patients the impact of 4-drug therapy on the viability of M. tubercle in their sputum was assessed. Viable tubercle bacilli continue to be excreted in patients with cavitating pulmonary disease on treatment for up to 9 weeks. It is suggested that patients with cavitating disease should probably not be allowed to return to high density accommodation for the elderly until their sputum is clear of acid fast bacilli on sputum smear examinations. The usefulness of using annual tuberculin skin reaction (Mantoux) tests as a screening procedure was evaluated in 648 residents in old age homes. The criteria for further investigation for pulmonary tuberculosis was either recent conversion to positive (reaction equal to 10 mm or more) or a year-on-year increase of greater than 12 mm, or any reaction> 20 mm. 206 subjects were identified as "possibly having the disease" and of these the diagnosis of pulmonary tuberculosis confirmed in 13 cases. 10/13 patients had Mantoux reactions of greater than 20 mm and 3/13 between 10 mm and 19 mm. As a result of this study the recommendation is made that a yearly Mantoux test is a useful screening procedure, and will help identify a population who should be further investigated with chest radiographs and sputum cultures.